The Impact of Other-Regarding Preferences on Moral Hazard and Adverse Selection - Thomas Daske (Technische Universität München, 2017)
This dissertation explores the role of other-regarding preferences in the form of altruism, spite, or status considerations in the resolution of adverse selection and moral hazard. Two chapters reflect upon the implications of asymmetric information on other-regarding preferences for incentive mechanism design in general and human resource management in specific. A third chapter reflects upon how moral hazard in the presence of other-regarding preferences may generate and shape people's ethical convictions regarding their abidance by social norms and formal law. Implications for public economic policy are drawn. – – Diese Dissertation untersucht die Rolle sozialer Präferenzen in der Form von Gunst, Missgunst oder Statusstreben für die Aufhebung von adverser Selektion und moralischem Risiko (moral hazard). Zwei Kapitel diskutieren die Konsequenzen von asymmetrischer Information über soziale Präferenzen für das Design von Anreizmechanismen im Allgemeinen und für Problemstellungen des Personalmanagements im Besonderen. Ein drittes Kapitel diskutiert, wie moralisches Risiko in Anwesenheit sozialer Präferenzen zur (Aus-)Prägung ethischer Überzeugungen im Hinblick auf die Einhaltung sozialer Normen führen kann. Politikimplikationen werden jeweils aufgezeigt.
urn:nbn:de:bvb:91-diss-20171121-1356815-1-6
Keywords: 650